Dental caries and social determinants of health in Mexico - Guillermo Cruz Palma; Rosa Isela Sánchez Najera; Miguel Ángel Quiroga García; Carlos Galindo Lartigue; Gustavo Israel Martínez González (Editorial Ciencias Médicas, 2014)
Dental caries is a multifactorial disease which represents a public health problem globally and nationally. There are known individual risk factors, not the population associated with its occurrence; it is not clear why some countries or regions have higher prevalence than others. It is necessary to analyze the Social Determinants of Health (SDH) associated. The aim of this study was to explore the association between some population determinants and the prevalence of dental caries in Mexican children. A case study of ecological character whose observation units were the 32 states of Mexico was conducted. A qualitative comparative analysis was conducted, using data from 2001National Survey of Dental Caries, and official data on income inequality (G), gross domestic product (P), percentage of illiterate population (A), percentage of rural population (R), percentage of indigenous population (I), net migration rate (L), indicated distribution of iodized salt fluoridated by state(F). The most common settings were GpARIlF (17.86 % of the states); gPariLF (14.29 %); GpARIlf (10.71 %) and gPariLf (7.14 %). When reducing a 0.80Benchmark, 0.900 and consistency and 0.463 of coverage were obtained with ten settings. A 0.90 Benchmark, 0.974 of consistency and 0.223 of coverage were obtained with four settings. The income inequality consistently participates in causal models of caries prevalence; distribution of iodized and fluoridated salt was negatively involved indicating its presence as a protective factor against the disease. It is suggested supporting actions to reduce income inequality, as well as to continue the distribution policy of fluoridated and iodized salt.